COVID-19 Vaccines Programs: adverse events following immunization (AEFI) among medical Clerkship Student in Jember, Indonesia - Supangat; Elly Nurus Sakinah; Muhammad Yuda Nugraha; Tegar Syaiful Qodar; Bagus Wahyu Mulyono; Achmad Ilham Tohari (BMC, 2021)
Abstract Introduction Coronavirus Disease (COVID-19) caused by Novel Coronavirus named as Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) was declared Pandemic by The World Health Organization (WHO) and a Public Health Emergency of International Concern (PHEIC) on January 30, 2020. Many COVID-19 vaccines have been developed, including CoronaVac vaccines by Sinovac. Health care workers, along with medical clerkship students are the priority to receive the vaccine. However, the Adverse Events Following Immunization (AEFI) of the CoronaVac remains unclear. This study aims to describe and analyze the adverse events following immunization (AEFI) of COVID-19 vaccination in medical students in clerkship programs. Method We conducted a cross-sectional study using a questionnaire to assess AEFI after CoronaVac vaccination among medical clerkship students. A Chi-Square test with 95 % of CI was used to determine whether gender correlated with symptoms of AEFI. Result We identified 144 medical clerkship students. The most common AEFI of SARS-CoV-2 vaccinations was localized pain in the injection site during the first dose with 25 (45 %) reports and the booster dose with 34 (67 %) reports. Then followed by malaise, the first dose with 20 (36 %) reports and the booster dose with 21 (41 %) reports. Other symptoms like headache, fever, shivering, sleepiness, nausea, dysphagia, and cold were also reported. Conclusions CoronaVac SARS-COV-2 vaccine has several mild symptoms of AEFI and not correlated with gender. Nevertheless, follow-up after vaccination is needed to prevent immunologic responses that may occur in some patients.